2021
DOI: 10.46237/amusbfd.775726
|View full text |Cite
|
Sign up to set email alerts
|

Göç ve Kadın Sağlığı Hizmetleri

Abstract: Son yıllarda, insanlık tarihi kadar eski ve evrensel bir olgu olan göç bazı ülkelerde oldukça artmıştır. 2019 yılında tüm uluslararası göçmenlerin üçte biri sadece on ülkeden göç etmiştir. Suriye 8.2 milyon vatandaşının göç etmesi ile bu on ülke arasında birinci sıradadır. Türkiye, Suriye ile sınır komşuluğu nedeni ile son on yılda Suriye'den en fazla göç alan ülkedir. Ülkemiz, 2011 Suriye krizinden sonra, 3.6 milyon Suriye'den göçmene ev sahipliği yapmaktadır. Ülkemizde bulunan 1.651.627 göçmen kadının 820.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 26 ] Various studies conducted in Turkey have shown that Syrian immigrant pregnant women have difficulties in accessing prenatal care services and have low rates of prenatal care (73.3%). [ 28 – 30 ] The rate of prenatal care for pregnant women in Turkey is 96.1%. [ 31 ] The rate of prenatal care in our research group is very close to the rate in Türkiye.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Various studies conducted in Turkey have shown that Syrian immigrant pregnant women have difficulties in accessing prenatal care services and have low rates of prenatal care (73.3%). [ 28 – 30 ] The rate of prenatal care for pregnant women in Turkey is 96.1%. [ 31 ] The rate of prenatal care in our research group is very close to the rate in Türkiye.…”
Section: Discussionmentioning
confidence: 99%